Neurocognitive rehabilitation of Down syndrome : the early years - Rondal, J. A.; Perera, Juan; Spiker, Donna (Cambridge University Press, 2011)
"Down syndrome is one of the most commonly occurring developmental disorders and it is now possible to conceptualize and define opportunities for neurocognitive rehabilitation for those with the condition. This book describes how early cognitive intervention in children with Down syndrome can be carried out, and can reduce, or compensate for, the major deficits characteristic of the condition. This comprehensive account relates the neurocognitive approach to the major therapeutic endeavors in the neighboring fields of neurogenetics, experimental environmental enrichment, molecular genetics, pharmacology, pediatrics and cardiology for infants with Down syndrome. Neurocognitive Rehabilitation of Down Syndrome provides the guidance required to establish effective rehabilitation programs, and is essential reading for developmental clinicians, pediatricians, neuropsychologists and other health professionals"--Provided by publisher.